2014
DOI: 10.1016/j.str.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of a Point Mutation that Causes the Genetic Disease Aspartylglucosaminuria

Abstract: Summary Aspartylglucosaminuria (AGU) is a lysosomal storage disease caused by a metabolic disorder of lysosomes to digest Asn-linked glycoproteins. The specific enzyme linked to AGU is a lysosomal hydrolase called glycosylasparaginase. Crystallographic studies revealed that a surface loop blocks the catalytic center of the mature hydrolase. Autoproteolysis is thus required to remove this P-loop and open up the hydrolase center. Nonetheless, AGU mutations result in misprocessing of their precursors and are defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…In the case of the mutant AGA precursors, this rearrangement is severely reduced, preventing the cleavage into subunits. It has been shown that dimerization of two precursor molecules is a prerequisite for the cleavage, and some AGU mutations in the dimer interface prevent dimerization and thus activation22930. However, this appears not to be the case with T122K and AGU-Fin, which both become processed into subunits when coexpressed with the wildtype AGA.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the mutant AGA precursors, this rearrangement is severely reduced, preventing the cleavage into subunits. It has been shown that dimerization of two precursor molecules is a prerequisite for the cleavage, and some AGU mutations in the dimer interface prevent dimerization and thus activation22930. However, this appears not to be the case with T122K and AGU-Fin, which both become processed into subunits when coexpressed with the wildtype AGA.…”
Section: Discussionmentioning
confidence: 99%
“…We also propose a plausible explanation for its low activity based on comparison of substrate bound complexes of the mutant model with the wildtype GA model. Since a precursor structure of the same mutant in complex with β-AHA has also been reported previously [17], in this study we further built a GA-β-AHA model complex by superposing a few GA structures: the current model, the precursor-β-AHA complex, and the wild-type GA structures [7, 17]. This allows us to analyze catalysis of β-AHA as a non-chitobiose substrate of GA.…”
Section: Introductionmentioning
confidence: 86%
“…The β-AHA-GA complex model was generated by superimposing secondary structure of G172D-β-AHA complex (precursor structure, PDB code 4R4Y) [17] with the previously published T152C GA-NAcGlc-Asn complex (GA-substrate structure, PDB code 2GL9) [23]. The coordinates of the β-AHA were then placed in the active site of the wild-type GA structure, built as described previously (2GAW) [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed mutagenesis and expression studies in COS cells demonstrated that only the cysteine to serine substitution (C163S) causes the deficiency of glycosylasparaginase activity [30]. The mutation destroys a disulfide bond [31] and leads to conformational changes in the inactive prercursor enzyme protein preventing its autocleavage into subunits and an active enzyme protein [32]. …”
Section: Molecular Geneticsmentioning
confidence: 99%